2006
DOI: 10.1021/cm060212g
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Processing Approach to Molecular Surface Tailoring of Nanoparticles:  Improved Photocatalytic Activity of TiO2

Abstract: Plasma enhanced chemical vapor deposition (PECVD) was employed to modify surfaces of TiO2 nanoparticles. To help overcome nanoparticle aggregation, a 360° rotating reactor was employed to provide continuous agitation and mixing of the particles during the plasma induced film deposition process. The nanoparticles were coated with thin films produced from the plasma polymerization of tetramethyltin (TMT) monomer. Subsequently, the coated particles were heated in air to remove the carbonaceous material while, sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 27 publications
(29 reference statements)
0
27
0
Order By: Relevance
“…These monomers were selected to provide a diverse variety of chemistries ranging from uncharged hydrophobic (C 6 F 14 ) and hydrophilic (EO 2 V), to cationic (VAA) and anionic (NH 2 C 2 H 4 NH 2 ) hydrophilic surfaces. A home built custom reactor, capable of continuous 360° rotation during the plasma deposition was employed to overcome the tendency for particle aggregation and thus promote more uniform polymer film coverage of the substrates [37,38]. One gram samples of the particles were coated in each run.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These monomers were selected to provide a diverse variety of chemistries ranging from uncharged hydrophobic (C 6 F 14 ) and hydrophilic (EO 2 V), to cationic (VAA) and anionic (NH 2 C 2 H 4 NH 2 ) hydrophilic surfaces. A home built custom reactor, capable of continuous 360° rotation during the plasma deposition was employed to overcome the tendency for particle aggregation and thus promote more uniform polymer film coverage of the substrates [37,38]. One gram samples of the particles were coated in each run.…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory has recently developed a modified Radio Frequency Glow Discharge (RFGD) technique to functionalize a wide variety of micro [37], and more recently, nanosized, spheres [38]. Additionally, using a pulsed plasma technique, we have previously shown that we can effectively control the film chemistry obtained from a given monomer undergoing polymerization via simple variations in the plasma duty cycles employed.…”
Section: Introductionmentioning
confidence: 99%
“…This efficient mass transport and agitation of the particles successfully overcomes the tendency for nanoparticle aggregation providing continuous exposure of fresh TiO 2 surface to the plasma generated reactive molecules and ions. The specific process employed has been previously shown to be extremely effective in coating fine powders [31], including nanoparticles [32]. In a typical run, 3.5 g of TiO 2 particles were loaded inside the borosilicate glass reactor and the reactor was evacuated to 5 mTorr background pressure.…”
Section: Tio 2 Particle Coatingmentioning
confidence: 99%
“…Under the pulsed condition, the extent of retention of the functional group in a given monomer increases as the duty cycle employed during the plasma polymerization is decreased [32]. The average power input is defined as: Average power (W) = (Duty cycle) × Peak Power (W), where the duty cycle represents the ratio of the plasma on time divided by the plasma (on + off) time.…”
Section: Polymer Characterizationsmentioning
confidence: 99%
“…To obtain partially fluorinated tin oxide, hexafluoropropylene oxide (C 3 F 6 O) was added to Sn(CH 3 ) 4 . It should be noted that significantly increased photocatalytic activity of TiO 2 nanoparticles was achieved using the PECVD approach (Cho, J. et al, 2006).…”
Section: Water Splitting Systemsmentioning
confidence: 99%